CORRECTIVE FEEDBACK AND CLASSROOM INTERACTION AT SMA 1 PAYAKUMBUH SUMATERA BARAT - Sahyoni Sahyoni (Ta'dib, 2018)
The main focus of this research is to investigate corrective feedback made by the English teacher during classroom interaction. The study was qualitative research. The data in this study were the utterances that spoken by teacher and student during the classroom activity. The data were collected through a record where the writer himself recorded the utterances during teaching learning process a ninety-minute in duration. In this study, the teacher is an English teacher who teaches at grade XI SMA Payakumbuh. The data were analyzed by qualitative approach, writer explained corrective feedback types that happened in classroom interaction. There are six types of corrective feedback occurred in the classroom interaction at SMA 1 Payakumbuh namely: recast, repetition, clarification request, explicit correction, elicitation, and paralinguistic correction. Recast, clarification request and elicitation are the most corrective feedback applied by teacher in the classroom interaction.